Near-Field Stationary Sample Terahertz Spectroscopic Polarimetry for Biomolecular Structural Dynamics Determination - Deng, Y.; McKinney, J. A.; George, D. K.; Niessen, K. A.; Sharma, A.; Markelz, A.G. (ACS Photonics, 2021)
THz polarimetry on environmentally sensitive and microscopic samples can provide unique insight into underlying mechanisms of complex phenomena. For example, near-field THz anisotropic absorption successfully isolated protein structural vibrations which are connected to biological function. However, to determine how these vibrations impact function requires high throughput measurements of these complex systems, which is challenged by the need for near field detection, sample environmental control and full polarization variation. Stationary sample anisotropic terahertz spectroscopy (SSATS) and near-field stationary sample anisotropic terahertz microscopy (SSATM) have been proposed using synchronous control of THz and electro optic probe polarizations along an iso-response curve. Here we realize these techniques through robust control and calibration of the THz and NIR polarization states. Both methods rapidly measure the linear dichroism in the far field and near field. Validation measurements using standard birefringent sucrose single crystals found the crystal orientation can be determined by scanning the reference polarization and the synchronous pump–probe polarization settings can be optimized to eliminate artifacts. SSATM is then used to determine spectral reproducibility and dehydration effects for a series of chicken egg white lysozyme samples. Reproducible anisotropic absorbance bands are found at about 30, 44, 55, and 62 cm–1. These bands initially sharpen with slow dehydration, similar to the increase in resolution achieved in X-ray crystallographic protein structure determination. The SSATM technique confirms the reliability of anisotropic absorption characterization of protein intramolecular vibrations and opens an avenue for rapid determination of how these long-range dynamics affect biological function.

Phonon Kinetics of Fructose at the Melting Transition - A. Davie; F. Vandrevala; S. Dampf; Y. Deng; D. K. George; E. D. Sylvester; T. Korter; E. Einarsson; J. B. Benedict; A. G. Markelz (J. Phys. Chem. C, 2021)
Terahertz time domain spectroscopy (THz TDS) is used to measure the melting kinetics of fructose molecular crystals. Combining single-crystal anisotropy measurements with density functional calculations, we assign the phonon frequencies and interrogate how specific phonons behave with melting. While nearly all the low-frequency phonons continuously red-shift with heating and melting, the lowest-energy phonon polarized along the c-axis blue-shifts at the melting temperature, suggesting an initial structural change immediately before melting. We find that the kinetics follow a 3D growth model with large activation energies, consistent with previous differential scanning calorimetry (DSC) measurements. The large activation energies indicate that multiple H-bonds must break collectively for the transition. The results suggest the generality of the kinetics for molecular crystals and that THz TDS with picosecond resolution could be used to measure ultrafast kinetics.

Evidence of Intramolecular Structural Stabilization in Light Activated State of Orange Carotenoid Protein - McKinney, J. A.; Sharma, A.; Crossen, K.; Deng, Y.; George, D. K.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. G. (Biophysical Journal, 2020)
Orange carotenoid protein (OCP) controls efficiency of the light harvesting antenna, the phycobilisome (PBS), in diverse cyanobacteria and prevents oxidative damage. It is the only known photoactive protein that uses a carotenoid, canthaxanthin, as its chromophore. The structure of OCP consists of two globular domains, connected by an unstructured loop, that forms a hydrophobic pocket for the carotenoid. In low light, canthaxanthin bound OCP is inactive and appears orange. Illumination by strong light results in an active state that interacts with the PBS to induce fluorescence quenching, a red appearance and conformational changes that include a 12Å shift by canthaxanthin into the N-terminal domain. Terahertz (THz) dynamical transition measurements and anisotropic terahertz microscopy are used to measure the intramolecular structural dynamics in the inactive and active states, which can be induced by photoexcitation or chaotropic salts. The measurements indicate that the active state has a decrease in structural flexibility, which may be related to enhanced interactions with the PBS.
Keywords: Biophysics

Linear dichroism infrared resonance in overdoped, underdoped, and optimally doped cuprate superconductors - Mukherjee, A.; Seo, J.; Arik, M. M.; Zhang, H.; Zhang, C. C.; Kirzhner, T.; George, D. K.; Markelz, A. G.; Armitage, N. P.; Koren, G.; Wei, J. Y. T.; Cerne, J. (Physical Review B, 2020)
By measuring the polarization changes in terahertz, infrared, and visible radiation over an extended energy range (3-2330 meV), we observe symmetry breaking in cuprate high-temperature superconductors over wide energy, doping, and temperature ranges. We measure the polarization rotation (Re[theta(F)]) and ellipticity (Im[theta(F)]) of transmitted radiation through thin films as the sample is rotated. We observe a twofold rotational symmetry in theta(F), which is associated with linear dichroism (LD) and occurs when electromagnetic radiation polarized along one direction is absorbed more strongly than radiation polarized in the perpendicular direction. Such polarization anisotropies can be generally associated with symmetry breakings. We measure the amplitude of the LD signal and study its temperature, energy, and doping dependence. The LD signal shows a resonant behavior with a peak in the few hundred meV range, which is coincident with the midinfrared optical feature that has been associated with the formation of the pseudogap state. The strongest LD signal is found in underdoped films, although it is also observed in optimally and overdoped samples. The LD signal is consistent with an electronic nematic order which is decoupled from the crystallographic axes as well as novel magnetoelectric effects.
Keywords: Materials Science; Physics

Is the Protein Dynamical Transition useful? - Sharma, A.; George, D. K.; Crossen, K.; McKinney, J.; Kerfeld, C.; Markelz, A. (Biophysical Journal, 2020)

Stabilization of Terahertz Vibrational Modes in Illuminated Orange Carotenoid Protein Crystals - McKinney, J.; Sharma, A.; Deng, Y.; George, D.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. (2020 45th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2020)
Orange carotenoid protein (OCP) controls efficiency of the phycobilisome (PBS), the light harvesting antenna in cyanobacteria, to prevent oxidative damage. The OCP switches from resting state to photo protective state with intense blue light illumination. Questions persist as to why OCPR interaction increases with the PBS over that with the OCPO. Here we examine the role of long-range intramolecular vibrations within OCP. Using Stationary Sample Anisotropic Terahertz Microscopy (SSATM) we measure changes in the intramolecular vibrations with photo switching. We report the first observation of switching in the intramolecular vibrations with photoexcitation. Results suggest that there is a stiffening of the molecule in the photo protective state. This increase in structural stability may enhance the interaction with the PBS change in OCP interaction with PBS. In low light, carotenoid bound OCP appears orange (OCP o ) and is inactive. Illumination by strong light converts OCP to the active, red (OCPR) state, which interacts with the PBS. A comparison of anisotropic THz microscopy measurements of dark adapted (OCP o ) and illuminated OCP crystals indicate differences in their vibrational modes that may be important for OCP-PBS interactions.

Anisotropic Terahertz Microscopy of Protein Collective Vibrations: Crystal Symmetry and Hydration Dependence - McKinney, J.; Deng, Y. T.; Sharma, A.; George, D. K.; Markelz, A. G. (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
A stationary sample anisotropic terahertz microscopy technique is used to characterize the intramolecular vibrations for lysozyme. Tetragonal and triclinic crystals are compared. We find excellent reproducibility within a single crystal symmetry group. Several resonant bands are present for both symmetry groups, indicating they originate with the intramolecular vibrations and not crystal lattice phonons. Bands become more pronounced and higher frequency resonant bands begin to emerge with slight dehydration.

Blue Shift of a Molecular Crystal Phonon at the Solid to Liquid Phase Transition - Davie, Alex; Vandrevala, Farah; Deng, Yanting; George, D.; Sylvester, Eric D.; Korter, T.; Einarsson, E.; Benedict, Jason B.; Markelz, Andrea (Bulletin of the American Physical Society, 2019)

Protein and RNA dynamical fingerprinting - Niessen, Katherine A; Xu, Mengyang; George, Deepu K; Chen, Michael C; Ferré-D’Amaré, Adrian R; Snell, Edward H; Cody, Vivian; Pace, James; Schmidt, Marius; Markelz, Andrea G (Nature communications, 2019)

Stationary Sample Anisotropic THz Spectroscopy using Discretely Tunable THz Sources - LaFave, T., Jr.; George, D. K.; Markelz, A. G.; McNee, Ian; Kozlov, Vladimir; Schunemann, Peter (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We demonstrate anisotropic THz spectroscopy of sucrose using newly developed compact discretely tunable THz sources for turn-key spectroscopic systems.

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Tunable narrow band sources for anisotropic THz spectroscopy - George, D. K.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P.; Markelz, A. G. (APS S23-002, 2019)

Tunable narrowband THz generation in orientation patterned gallium phosphide for THz anisotropy identification - McNee, I.; Tekavec, P.; Kozlov, V.; Markelz, A. G.; George, D. K.; Schunemann, P. (Nonlinear Frequency Generation and Conversion: Materials and Devices Xviii, 2019)
We demonstrate tunable narrowband THz generation by optical rectification of a femtosecond pulse in Orientation Patterned Gallium Phosphide. Center frequencies of 0.9 - 3.8 THz with average power up to 15 mu W were achieved using a 1.064 mu m fiber laser for the pump laser. Biomolecular characterization for an early application of this system is also shown in this work by anisotropic spectroscopic signature detection of molecular crystals in the THz region.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

THz Anisotropy Identification using Tunable Compact Narrow Band THz Sources - George, D. K.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (2018 43rd International Conference on Infrared, Millimeter, and Terahertz Waves, 2018)
We demonstrate THz anisotropy signature determination of a protein crystal model using newly developed compact tunable narrow band THz sources for turn-key spectroscopic systems for the bio molecular community.

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Importance of Protein Vibration Directionality on Function - Niessen, Katherine A.; Xu, Mengyang; Deng, Yanting; Snell, Edward H.; Markelz, Andrea G. (Biophysical Journal, 2017)

Moving in the right direction: protein vibrations steering function - Niessen, Katherine A; Xu, Mengyang; Paciaroni, Alessandro; Orecchini, Andrea; Snell, Edward H; Markelz, Andrea G (Biophysical Journal, 2017)

Anisotropic Absorption Measurements Reveal Protein Dynamical Transition in Intramolecular Vibrations - Xu, M. Y.; Niessen, K.; Michki, N.; Deng, Y. T.; Snell, E.; Markelz, A. G. (2016 41st International Conference on Infrared, Millimeter, and Terahertz Waves, 2016)
Modeling has predicted that intramolecular structural vibrations enables proteins to access functionally important structural change. We show that the vibrational density of states and the isotropic absorption in the terahertz range are only weakly dependent on the protein functional state for several bench marking proteins. At the same time the direction of motions changes dramatically with functional state and with a resulting impact on the anisotropic absorption. Our anisotropic THz microscopy (ATM) measurements confirm this sensitivity. Here we apply the technique to the question of whether the protein dynamical transition (DT) is important to protein function. We find a strong anisotropic resonance at 70 cm(-1) rapidly increases in strength at temperatures above the DT. As these intramolecular vibrations enable protein structure to change conformation, the results suggest function will cease below DT for those proteins that require large scale conformational change.

Direct Measurements of the Long-Range Collective Vibrations of Photoactive Yellow Protein - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A.; Schmidt, Marius; Markelz, Andrea G. (30th Anniversary Symposium of The Protein Society, 2016)
Long-range collective vibrations are thought to be crucial to protein functions. In the case of photoactive protein family, modeling suggests the intramolecular vibrations provide an efficient means of energy relaxation[1], feedback for enhancement of chromophore vibrations that promote structural transitions[2] and can assist in charge energy transfer[3]. As a paradigm of this family, photoactive yellow protein (PYP) is a cytoplasmic photocycling protein related to negative phototactic response to blue light in purple photosynthetic bacteria. PYP has a p-coumaric acid chromophore binding to the cysteine residue via a thioester bond, whose vibrations were found to overlap calculated vibrations of the protein scaffold. Using our unique technique of anisotropic terahertz microscopy(ATM)[4], we measure the intramolecular vibrations for PYP for the first time, including cycling between ground and blue shift (pB) states. Room temperature ATM measurements are performed in the dark and with continuous wave illumination at 488nm, resulting in a steady pB state with approximately 5% population conversion. In pB state, we find an overall decrease in the strength of resonant band in frequency range of 30-60 cm-1. Our calculated spectra using quasi-harmonic analysis indicate that our measurements are dominated by the protein vibrations, rather than the pCA chromophore, allowing us to characterize how the scaffold dynamics changes with functional states and mutations. 1. Levantino, M., et al. Nat Commun, 2015. 6. 2. Mataga, N., et al. Chem. Phys. Lett., 2002. 352(3-4): p. 220-225. 3. Fokas, A.S., et al. Photosynth. Res., 2014. 122

Modulated orientation-sensitive terahertz spectroscopy - Singh, R.; George, D. K.; Bae, C. J.; Niessen, K. A.; Markelz, A. G. (Photonics Research, 2016)
Intramolecular vibrations of large macromolecules reside in the terahertz range. In particular, protein vibrations are closely spaced in frequency, resulting in a nearly continuous vibrational density of states. This density of vibrations interferes with the identification of specific absorption lines and their subsequent association with specific functional motions. This challenge is compounded with the absorption being dominated by the solvent and local relaxational motions. A strategy for removing the isotropic relaxational loss and isolating specific vibrations is to use aligned samples and polarization-sensitive measurements. Here, we demonstrate a technique to rapidly attain the anisotropic resonant absorbance using terahertz time domain spectroscopy and a spinning sample. The technique, modulated orientation-sensitive terahertz spectroscopy (MOSTS), has a nonzero signal only for anisotropic samples, as demonstrated by a comparison between a silicon wafer and a wire grid polarizer. For sucrose and oxalic acid molecular crystals, the MOSTS response is in agreement with modeled results for the intermolecular vibrations. Further, we demonstrate that, even in the presence of a large relaxational background, MOSTS isolates underlying vibrational resonances. (C) 2016 Chinese Laser Press
Keywords: absorption-spectroscopy; dynamics; enzyme catalysis; low-frequency modes; lysozyme; neutron-scattering; Optics; perspective; polarization modulation; proteins; water

The Role of Dynamical Transition in Protein Function: Coupling of Protein Collective Vibrations and Water Dynamics - Xu, Mengyang; Niessen, Katherine; Deng, Yanting; Michki, Nigel; Snell, Edward; Markelz, Andrea (30th Anniversary Symposium of The Protein Society, 2016)
Computational simulations have revealed protein collective vibrations prompt structural rearrangements to accomplish biological function. However, the biological importance of collective vibrations has not been experimentally demonstrated. The attempts have been hampered by the inability to distinguish localized water or side-chain relaxational motions from protein long-range vibrations using conventional techniques. The dynamical transition (DT), extensively observed using X-ray, neutron scattering, NMR and terahertz techniques [1,2], describes a rapid increase in the temperature-dependent dynamics of critically hydrated proteins above ∼220 K, and has been attributed to thermally activated solvent motions. While some proteins lose function below the specific temperature, others do not. We suggest the difference arises from the nature of the required motions for function. Specifically, functional motions enabled by long-range vibrations will be vulnerable to DT, which require surrounding solvent to be sufficiently mobile. We explored the coupling of protein vibrations to solvent dynamics by applying a recently developed technique, anisotropy terahertz microscopy [3], to directly measure the collective vibrations for lysozyme and investigate the temperature dependence in 150-300 K range. We find long-range intramolecular vibrations occur at 220K and rapidly increase in strength with increasing temperature, consistent with enhanced access above the DT. The results suggest collective vibrations are slaved to DT, and those proteins with function reliant on these motions will cease function below DT. 1. Doster,W., et al. Phys.Rev.Lett., 2010.104(9):098101. 2. Niessen,K., et al. Biophys.Rev., 2015.7,201. 3. Acbas,G., et al. Nat.Commun., 2014.5,3076.

Measurements and Calculations of Protein Intramolecular Vibrations in the THz Range - Niessen, K. A.; Snell, E.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
We report the calculations and measurements of intramolecular vibrational modes and their dependence on inhibitor binding in the THz range. We see an increase in anisotropic THz absorption at low frequency with inhibitor binding in both the measurements and calculations. This surprising result suggests an increase in flexibility with binding. We will discuss the possible reasons for this discrepancy.
Keywords: charmm

Optical measurements of long-range protein vibrations - Acbas, G.; Niessen, K. A.; Snell, E. H.; Markelz, A. G. (Nature Communications, 2014)
Protein biological function depends on structural flexibility and change. From cellular communication through membrane ion channels to oxygen uptake and delivery by haemoglobin, structural changes are critical. It has been suggested that vibrations that extend through the protein play a crucial role in controlling these structural changes. While nature may utilize such long-range vibrations for optimization of biological processes, bench-top characterization of these extended structural motions for engineered biochemistry has been elusive. Here we show the first optical observation of long-range protein vibrational modes. This is achieved by orientation-sensitive terahertz near-field microscopy measurements of chicken egg white lysozyme single crystals. Underdamped modes are found to exist for frequencies >10 cm(-1). The existence of these persisting motions indicates that damping and intermode coupling are weaker than previously assumed. The methodology developed permits protein engineering based on dynamical network optimization.
Keywords: absorption; crystals; dynamics; frequency raman-spectra; hydration; lysozyme; motions; Science & Technology - Other Topics; sensitivity; simulations; spectroscopy

Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz

Improved mode assignment for molecular crystals through anisotropic terahertz spectroscopy - Singh, Rohit; George, Deepu Koshy; Benedict, Jason B; Korter, Timothy M; Markelz, Andrea G (The Journal of Physical Chemistry A, 2012)

Multi-component response in multilayer graphene revealed through terahertz and infrared magneto-spectroscopy - Ellis, C. T.; Stier, A. V.; George, D. K.; Tischler, J. G.; Glaser, E. R.; Myers-Ward, R. L.; Tedesco, J. L.; Eddy, C. R.; Gaskill, D. K.; Markelz, A. G.; Cerne, J. (37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)

Orientation Sensitive Terahertz Resonances Observed in Protein Crystals - Acbas, G.; Snell, E.; Markelz, A. G. (2012 37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)
A method is presented for measuring anisotropic THz response for small crystals, Crystal Anisotropy Terahertz Microscopy (CATM). Sucrose CATM measurements find the expected anisotropic phonon resonances. CATM measurements of protein crystals find the expected broadband water absorption is suppressed and strong orientation and hydration dependent resonant features.
Keywords: dynamics; mode

Terahertz magneto-optical polarization modulation spectroscopy - George, Deepu K; Stier, Andreas V; Ellis, Chase T; McCombe, Bruce D; Černe, John; Markelz, Andrea G (JOSA BJOSA B, 2012)

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
Keywords: bi2te3; Physics

Magneto Optical Polarization Measurements using THz Polarization Modulation Spectroscopy - Stier, A. V.; George, D.; Markelz, A. G.; Cerne, J. (2011 36th International Conference on Infrared, Millimeter, and Terahertz Waves, 2011)
We report a new broad band technique for rapidly measuring the complex Faraday and Kerr rotations in materials such as topological insulators and graphene, combining the distinct advantages of THz time domain spectroscopy and polarization modulation techniques. The performance of the system is demonstrated using GaAs two dimensional electron gas in a magnetic field.

Characterization of Phonons in Molecular Crystals - Singh, R.; George, D.; Markelz, A. G. (Frontiers in Optics 2010, 2010)
We demonstrate a new technique for characterizing the phonons in molecular crystals, Modulated Orientation Sensitive Terahertz Spectroscopy (MOSTS). The technique suppresses crystal defects and solvent contributions, and enhances contributions due to molecular structure and anisotropy.

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Critical hydration and temperature effects on terahertz biomolecular sensing - Knab, Joseph; Shah, Binni; Chen, Jing-Yin; Markelz, Andrea (Chemical and Biological Standoff Detection III, 2005)

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Temperature of quasi-two-dimensional electron gases under steady-state terahertz drive - Asmar, N. G.; Cerne, J.; Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Campman, K. L.; Gossard, A. C. (Applied Physics Letters, 1996)
We use photoluminescence to study the time-average energy distribution of electrons in the presence of strong steady-state drive at terahertz (THz) frequencies, in a modulation-doped 125 Angstrom AlGaAs/GaAs square well that is held at low lattice temperature TL. We find that the energy distribution can be characterized by an effective electron temperature, T-e(>T-L), that agrees well with values estimated from the THz-illuminated, dc conductivity. This agreement indicates that under strong THz drive, LO phonon scattering dominates both energy and momentum relaxation; that the carrier distribution maintains a heated, thermal form; and that phonon drift effects are negligible. (C) 1996 American Institute of Physics.
Keywords: hot-electrons; Physics

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.

NONLINEAR QUANTUM DYNAMICS IN SEMICONDUCTOR QUANTUM-WELLS - Sherwin, M. S.; Craig, K.; Galdrikian, B.; Heyman, J.; Markelz, A.; Campman, K.; Fafard, S.; Hopkins, P. F.; Gossard, A. (Physica D-Nonlinear Phenomena, 1995)
We discuss recent measurements of the nonlinear response of electrons in wide quantum wells driven by intense electromagnetic radiation at terahertz frequencies. The theme is the interplay of quantum mechanics, strong periodic driving, the electron-electron interaction and dissipation. We discuss harmonic generation from an asymmetric double quantum well in which the effects of dynamic screening are important. Measurements and theory are found to be in good agreement. We also discuss intensity-dependent absorption in a 400 Angstrom square quantum well. A new nonlinear quantum effect occurs, in which the frequency at which electromagnetic radiation is absorbed shifts to the red with increasing intensity. The preliminary experimental results are in agreement with a theory by Zaluzny, in which the source of the nonlinearity is the self-consistent potential in the Hartree approximation for the electron dynamics.

QUENCHING OF EXCITONIC QUANTUM-WELL PHOTOLUMINESCENCE BY INTENSE FAR-INFRARED RADIATION - FREE-CARRIER HEATING - Cerne, J.; Markelz, A. G.; Sherwin, M. S.; Allen, S. J.; Sundaram, M.; Gossard, A. C.; Vanson, P. C.; Bimberg, D. (Physical Review B, 1995)

RESONANT-ENERGY RELAXATION OF TERAHERTZ-DRIVEN 2-DIMENSIONAL ELECTRON GASES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Cerne, J.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Physical Review B, 1995)

Far-infrared harmonic generation from semiconductor heterostructures - Markelz, A.G.; Gwinn, E. G.; Sherwin, M. S.; Heyman, J. N.; Nguyen, C.; Kroemer, H. (SPIE Proceedings, 1994)

FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.

GIANT 3RD-ORDER NONLINEAR SUSCEPTIBILITIES FOR INPLANE FAR-INFRARED EXCITATION OF SINGLE INAS QUANTUM-WELLS - Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Solid-State Electronics, 1994)
Third-order, free-carrier nonlinear susceptibilities, chi(3), have been measured between 19 and 23 cm-1 for three InAs/AlSb quantum wells with sheet densities between 2.5 x 10(12) cm-2 and 8 x 10(12) cm-2. We find that these wells are strongly nonlinear at far-infrared frequencies: odd harmonics ninth order have been observed at high incident intensities, and the peak value of chi(3) reaches approximately 1 esu. This is several orders of magnitude larger than previously reported values for chi(3) in bulk n-GaAs (10(-4) esu)[1] and in polyacetylene (10(-7) esu)[2]. The large magnitude of chi(3) is attributed to the high carrier density in the InAs wells, and to the strong non-parabolicity of the conduction band in InAs. However, the free-carrier chi(3) for bulk InAs predicts a density-dependence different from that observed, and the measured decrease in chi(3) with increasing intensity indicates non-perturbative response. We find that the anisotropy of chi(3) displays the expected 4-fold symmetry.

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.

SUBCUBIC POWER DEPENDENCE OF 3RD-HARMONIC GENERATION FOR INPLANE, FAR-INFRARED EXCITATION OF INAS QUANTUM-WELLS - Markelz, A. G.; Asmar, N. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Semiconductor Science and Technology, 1994)
Large third-order, free-carrier nonlinear susceptibilities, chi(3) (to approximately 0.2 esu), and subcubic dependence of the third-harmonic power on the incident intensity, have been observed between 19 cm-1 and 23 cm-1 for InAs/AlSb quantum wells with electron sheet densities between 2.5 x 10(12) cm-2 and 8 X 10(12) cm-2. We find that the transmission of the fundamental, and the samples' DC conductivity, decrease with increasing incident intensity, indicating a large rise in the scattering rate. Using the intensity-dependent transmission to account for absorption in the sample is not sufficient to recover a cubic power law for the third-harmonic intensity. In addition, given the increased scattering rate indicated by the conductivity data, the bulk free-carrier chi(3) due to non-parabolicity should decrease dramatically with increasing fundamental intensity, contrary to our results. Thus, non-parabolicity alone cannot account for the observed third-harmonic response.

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)